PENGARUH HARGA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOPI SECARA ONLINE (Studi Kasus Kopi Aceng Garut) - Kandida Ethania Nurhidayah; Ahmad Choibar Tridakusumah (Universitas Galuh, 2022)
Coffee consumption in Indonesia continues to increase in line with changes in people's lifestyles. However, due to the COVID-19 pandemic, people cannot buy coffee at cafes or coffee shops. This has prompted a change in the sales system where coffee products can be sold on social media and online sales platforms. The transfer of the sales system was felt by one of the coffee business units, namely Kopi Aceng. This study aims to determine the characteristics of consumers and analyze how the influence of price, brand image and product quality on online coffee purchasing decisions. This research is a quantitative research using survey method. The sample of this research is Kopi Aceng consumers who buy coffee online, totaling 100 people. The data analysis technique used multiple linear regression analysis. The results show that the majority of Kopi Aceng consumers are men with an age range of 26-35 years who live outside Garut, work as private employees and earn between Rp. 1.000.0000 – Rp. 5,000,000. The results showed that the variables of price, brand image and product quality had an influence on online purchasing decisions with product quality as the most influential variable in purchasing decisions at Kopi Aceng.